Manganese enhances the expression of the manganese superoxide dismutase in cultured primary chick embryonic myocardial cells - Shi-zhen QIN; Xiu-dong LIAO; Lin LU; Li-yang ZHANG; Lin XI; Yan-li GUO; Xu-gang LUO (Journal of Integrative Agriculture, 2017)
In the present study, the effect of manganese (Mn) on antioxidant status and the expression of the manganese superoxide dismutase (MnSOD) gene in cultured primary myocardial cells collected from the chick embryos was investigated. The hypothesis that Mn supplementation would enhance the expression of MnSOD in cultured primary myocardial cells of chick embryos was tested. Eggs collected from Mn-depleted Arbor Acres laying breeder hens were incubated for 10 days and then myocardial cells were isolated and cultivated for 8 days. The embryonic myocardial cells on day 6 were treated with Mn in the cell culture medium at different time points when the proportion of cells showing spontaneous contraction was over 95% after the 3-day primary culture. A completely randomized design involving a 3 Mn levels (0, 0.5 and 1.0 mmol L−1)×3 incubation time points (12, 24 and 48 h) factorial arrangement of treatments (n=6) was used in the current experiment. The results showed that MnSOD activity and mRNA expression level were induced by Mn and increased with incubation time, which supported the hypothesis that Mn would enhance the expression of the MnSOD gene, and thus might protect myocardial cells from oxidative stress during the chick embryonic development.